ANALISIS KEMAMPUAN LITERASI SISWA MELALUI ARISAN BUKU DI SD SWASTA PERKUMPULAN AMAL BHAKTI (PAB) 23 PATUMBAK - Ismahani; Zon Saroha Ritonga (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2019)
The low literacy skills of students are a serious problem in schools, so researchers apply the book gathering method. This method aims to encourage students to read more and be responsible for reading material. The book gathering method is intended so that students can regulate their desires regarding the books they read. Apart from that, teachers can also carry out various learning activities which are essentially to reactivate the library or reading corner in the classroom. This research is a qualitative descriptive research consisting of planning stages, collecting initial data, main data and final data, as well as completion. The research subjects were VA class students. Data was collected through interview, observation and documentation techniques. The validity of the data was obtained through a process of triangulation of sources and methods. Data analysis was carried out through coding and categorizing data as well as data interpretation. The results of the research show that children's literacy skills have shown a significant increase after implementing the book social gathering method. This is marked by the increasing awareness and need of children for books as a learning resource. In general, class V A students at PAB 34 Private Elementary School have achieved indicators of success in improving their literacy skills. This is characterized by high enthusiasm for the existence of books and the need for books. Evaluation is carried out through end-of-semester monitoring and evaluation using violation record instruments and monitoring observation results. The evaluation aspects include planning, completeness of facilities, implementation, achievement of targets and comparison of conditions.